Redução de CO2 a partir de reações de catálise homogênea com complexos bimetálicos de cobalto - Santos, Mayara Fontanelli dos (Universidade Federal de São Carlos, 2024)
This work addresses a topic of significant contemporary relevance: the growing concern about pollution caused by greenhouse gases, which exacerbate global warming and consequently result in extreme weather events in various regions worldwide. This study presents important data on homogeneous catalysis reactions and CO2 electroreduction, aiming to produce formaldehyde and methanol—compounds that are highly useful in the industry—using a bimetallic cobalt (II) complex as a catalyst. The research delves into the analysis of metallic complexes, providing detailed information on the coordination between the metal and the ligands, and justifying the choice of cobalt as the catalytic metal. In the context of CO2 reduction, different types of catalysis are explored, including photocatalysis and electrocatalysis, as well as the three main forms of CO2 capture: pre-combustion, post combustion, and direct air capture. By comparing with complexes reported in the literature, it is concluded that the CO2 reduction process using a bimetallic cobalt (II) complex is feasible. The presence of two metals in the complex offers significant advantages, enhancing the selectivity and efficiency of the catalytic process and the presence of the ligand can affect the stability.
Carbon Dioxide reduction with homogeneus reactions using bimetallic cobalt complexes
Keywords: Cobalto; Reducao de CO2; Catalise homogenea; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA